Renewable energy physics, engineering, environmental impacts, economics & planning - Sorensen, Bent. 1941- (Burlington, MA : Academic Press, 2011)
This volume is a true shelf reference, providing a thorough overview of the entire renewable energy sphere, while still functioning as a go-to information source for professionals and students when they need answers about a specific technical issue. Crafted over the last 15 years into a problem-solving tool for engineers, researchers, consultants and planners currently working in the field, as well as a detailed map of the renewables universe for those looking to expand into new technological specialties, Renewable Energy by Sorensen offers the most comprehensive coverage of the subject available. The book has been structured around three parts in order to assist readers in focusing on the issues that impact them the most for a given project or question. PART I covers the basic scientific principles behind all major renewable energy resources, such as solar, wind and biomass. PART II provides in-depth information about how these raw renewable sources can actually be converted into useful forms, transmitted into the grid and stored for future utilization. Finally, PART III undertakes the aspects of energy planning, environmental impacts and socio-economic issues on regional and global levels. In this fourth edition update, new material includes expanded coverage of biofuels, solar conversion, biomass and fuel cells, storage and transmission, and a new chapter on integrated technologies to introduce the hybrid systems now being explored. New surveys and the most recent research findings are included throughout. *New, thoroughly updated fourth edition of the authoritative field guide to the entire Renewable Energy universe *The only books to scientific principles and implementation methods, technologies and socio-economics, environmental impacts and cutting-edge advances, all in one volume. *New material includes expanded coverage of biofuels, solar conversion, biomass and fuel cells, storage and transmission, and a new chapter on integrated systems.
Frontmatter -- Chapter 1. Perspectives -- 1.1 Current marketplace penetration -- 1.2 Brief history of energy use -- 1.3 Determinants for the future development in energy use -- 1.4 Topics for discussion and for mini-projects -- PART I: Energy Resources -- Chapter 2. Status, prospects and sustainability issues -- 2.1 Non-renewable energy resources -- 2.2 Renewable energy resource introduction -- Chapter 3. The origin of renewable energy flows -- 3.1 Solar radiation -- 3.2 Disposition of radiation at the Earth -- 3.3 Processes near the surface of the Earth -- 3.4 Non-radiative energy flows -- 3.5 Topics for discussion and for mini-projects -- Chapter 4. Modelling renewable energy flows -- 4.1 Circulation modelling -- 4.2 Climate: definition and modelling -- 4.3 Climate: interference and change -- 4.4 Summary of energy and related matter cycles -- 4.5 Topics for discussion and for mini-projects -- Chapter 5. Individual renewable energy resources -- 5.1 Direct solar energy -- 5.2 Wind flows -- 5.3 Water flows and reservoirs, waves and tides -- 5.4 Heat flows and reservoirs -- 5.5 Biological conversion and stores -- 5.6 Topics for discussion and for mini-projects -- PART II: Technologies for converting and handling renewable energy -- Chapter 6. General principles -- 6.1 Principles of energy conversion -- 6.2 Thermodynamical engine cycles -- 6.3 Topics for discussion and for mini-projects -- Chapter 7. Heat energy conversion processes -- 7.1 Direct thermoelectric conversion -- 7.2. Engine conversion of solar energy -- 7.3 Heat pumps -- 7.4 Geothermal energy conversion -- 7.5 Ocean-thermal conversion -- 7.6 Topics for discussion and for mini-projects -- Chapter 8. Mechanical energy conversion processes -- 8.1 Basic description of flow-driven converters -- 8.2 Propeller-type converters -- 8.3. Cross-wind and other alternative converter concepts -- 8.4 Hydro and tidal energy conversion -- 8.5 Magneto hydrodynamic converters -- 8.6 Wave energy converters -- 8.7 Topics for discussion and for mini-projects -- Chapter 9. Solar radiation conversion processes -- 9.1 Photovoltaic conversion -- 9.2 Photo-electrochemical conversion -- 9.3 Solar thermal conversion -- 9.4 Solar thermal electricity generators -- 9.5 Solar cooling and other applications -- 9.6 Topics for discussion and for mini-projects -- Chapter 10. Electrochemical energy conversion processes -- 10.1 Fuel cell principles -- 10.2 Specific types of fuel cells -- 10.3 Other electrochemical energy conversion -- 10.4 Topics for discussion and for mini-projects -- Chapter 11. Bioenergy conversion processes -- 11.1 Combustion -- 11.2 Biological conversion into gaseous fuels -- 11.3 Biological conversion into liquid fuels -- 11.4 Thermochemical conversion to gaseous and other fuels -- 11.5 Topics for discussion and for mini-projects -- Chapter 12. Energy Transmission -- 12.1 Heat transmission -- 12.2 Power transmission -- 12.3 Fuel transmission -- 12.4 Topics for discussion and for mini-projects -- Chapter 13. Energy storage technologies -- 13.1 Heat capacity storage -- 13.2 Latent heat and chemical transformation storage -- 13.3 Pumped hydro storage -- 13.4 Flywheels -- 13.5 Hydrogen and other compressed gas storage -- 13.6 Battery storage -- 13.7 Additional storage forms -- 13.8 Topics for discussion and for mini-projects -- PART III: Planning and socio-economic issues -- Chapter 14. Energy system planning -- 14.1 The methodologies of energy planning -- 14.2 Demand scenario construction -- 14.3 Overall system scenarios -- 14.4 Consistency simulation and implementation studies -- 14.5 Local systems -- 14.6 Regional systems -- 14.7 Global systems -- 14.8 Topics for discussion and for mini-projects -- Chapter 15. Socio-economic assessment -- 15.1 Social and economic framework -- 15.2 Scale of analysis -- 15.3 Life-cycle approach -- 15.4 Assessment issues -- 15.5 Communication and policy dimensions -- 15.6 Topics for discussion and for mini-projects -- Chapter 16. Integrated approaches -- 16.1 Greenhouse warming mitigation -- 16.2 Greenhouse warming adaptation -- 16.3 Ecological sustainability -- 16.4 Winding up -- References -- Index.
Includes bibliographical references and index.
Keywords: Renewable energy sources; Electronic books